ANALYSIS OF THE IMPLEMENTATION OF EMOTION AI AS AN EMOTIONAL SUPPORT TOOL FOR UNIVERSITY STUDENTS - Pérez, Hólguer Rodrigo Altamirano; Galarza, Máximo Ortega; Arcos, Alisson Samara; Alcocer, Heidi Mikaela; Cajamarca, Deysi Carolina; Cadena, Daniela Alejandra; Méndez, Dana Alejandra; Tusa, Jaime Steven (Seven Editora, 2025)
Emotional artificial intelligence, or Emotion AI, has become one of the most disruptive changes in the field of technological education, allowing machines to recognize, analyze, interpret, and respond to human emotions. This technological advance has changed and transformed not only the way we act in the digital age, but also opens up new possibilities for application in environments where emotional well-being is crucial for individuals who are part of a job, study, and at the same time home life, such as students in the Accounting and Auditing program at the Faculty of Administrative Sciences of the Central University of Ecuador. The methodology applied was descriptive and explanatory, using a mixed approach and applying the deductive method. The information was processed in SPSS V25 in three phases for greater understanding. The instruments used were a survey of 60 students in their final semesters at the university, chosen for their proximity to the subject of study, and a literature review of 30 documents using the PRISMA methodology. The main results showed that 78% of students considered it likely or very likely that Emotion AI can contribute to improving emotional well-being in academic or work environments, and 63% of students indicated that academic and workloads affect their emotional state, with emotions such as stress and anxiety predominating. The main limitation facing this issue is the lack of awareness among teachers and authorities of the possible causes of student repetition. DOI: https://doi.org/10.56238/sevened2025.029-111